Automated exploration data analysis tool - Koh, Yu Bin (2025)
This project focuses on developing a web-based automated EDA tool This tool designed to simplify and streamline the EDA process. The primary objective is to automate the labour-intensive manual EDA procedures, eliminating the need for deep statistical or programming knowledge. The project addresses the limitations of existing tools, particularly for analyzing textual data by enhancing text data exploration capabilities. The system involves building a user-friendly interface using HTML for the front-end and Flask for back-end processing. Users can upload datasets and receive immediate visual and statistical analysis, including correlation heatmaps, bar charts, word clouds, and other visualizations tailored to numerical, categorical, and text data types. Text preprocessing features, such as tokenization and stop word removal are incorporated to handle textual data more effectively. The system will provide automatic insights based on dataset characteristics to reduce human error in data exploration. In summary, the tool can democratise data analysis by lowering the time and effort required for data preprocessing and visualisation while also making it available to a wider audience.